Penerapan Material Ramah Lingkungan pada Microlibrary Bima Kota Bandung: as Children's Education - Bella, Christa; Darmayanti, Tessa Eka (Program Studi Desain Interior Unikom, 2022)
This research is based on the author's anxiety about the behavior of indonesian people towards the use of single-use plastics to eventually cause a buildup of plastic waste. Damage to natural disasters often occurs due to the buildup of plastic waste, until finally the public realizes the importance of environmentally friendly education and recycling from an early age. Educating the community, especially children, about environmental friendliness can be started through adequate educational facilities. In this context, this study took the example of the design of The Bima Microlibrary located on Jalan Bima Utara Bandung City. Microlibrary Bima is a means of education in residential areas that is one of the alternatives to improve the quality of education, especially for children, who apply the use of environmentally friendly materials on the façade of buildings. Although during this pandemic Microlibrary Bima is not operating, it does not make it an obstacle that Microlibrary Bima is an interesting building to discuss. The type of research conducted is qualitative with descriptive analysis research methods. This paper provides an explanation of the importance of applying environmentally friendly materials in creating educational facilities as a real example for children to learn environmentally friendly concepts. The results of the analysis concluded that the design of Bima Microlibrary as an educational tool that applies environmentally friendly materials can be a real example for children to learn and realize the benefits of the importance of learning environmentally friendly concepts and contribute to developing the character of children who care about the environment. Keywords: Microlibrary Bima, environmental friendly, recycling, material